2021
DOI: 10.1080/21655979.2021.1971483
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Krüppel-like factor 5-regulated N-myc downstream-regulated gene 2 reduces IL-1β-induced chondrocyte inflammatory injury and extracellular matrix degradation

Abstract: Zhu (2021) Transcription factor Krüppel-like factor 5-regulated N-myc downstream-regulated gene 2 reduces IL-1β-induced chondrocyte inflammatory injury and extracellular matrix degradation, Bioengineered, 12:1, 7020-7032,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Indeed, overexpression of KLF5 counteracts the effect of NDRG2 on reducing the release of inflammatory cytokines by up-regulating the expression of a large number of proinflammatory cytokines (TNFα, IL-6, p-NF-κB p65 and Cox-2). 86 Overall, the aforementioned findings provide compelling evidence that aberrant expression levels of KLF2, KLF4 and KLF5, important OA regulatory factors, can impact the inflammatory pathological state of OA. KLF5 stimulates inflammation, while KLF2 and KLF4 are negative regulatory factors in OA inflammation.…”
Section: Klfs and Inflammatory Responsementioning
confidence: 88%
See 2 more Smart Citations
“…Indeed, overexpression of KLF5 counteracts the effect of NDRG2 on reducing the release of inflammatory cytokines by up-regulating the expression of a large number of proinflammatory cytokines (TNFα, IL-6, p-NF-κB p65 and Cox-2). 86 Overall, the aforementioned findings provide compelling evidence that aberrant expression levels of KLF2, KLF4 and KLF5, important OA regulatory factors, can impact the inflammatory pathological state of OA. KLF5 stimulates inflammation, while KLF2 and KLF4 are negative regulatory factors in OA inflammation.…”
Section: Klfs and Inflammatory Responsementioning
confidence: 88%
“…Likewise, KLF5 is up-regulated in IL-1β-induced ATDC5 chondrocytes. 86 N-myc downstream-regulated gene 2 (NDRG2) has been identified as a key biomarker and regulator of OA. 87 Mei et al 86 reported that KLF5 overexpression increased the expression of ECM degradation-related MMP3, MMP13 and ADAMTS4 levels, decreased collagen II expression and reversed the ameliorative effect of NDRG2 on ECM degradation.…”
Section: Klfs and The Degradation Of Ecmmentioning
confidence: 99%
See 1 more Smart Citation
“…The IL-1β pro-inflammatory cytokine is usually used to stimulate chondrocytes to undergo OA-like changes in vitro . NDRG2 expression is much lower in IL-1β–treated chondrocytes than in untreated cells, and its overexpression by transfection of pcDNA3.1(+)/NDRG2 restores the inflammatory response and ECM degradation in chondrocytes ( 48 ). Furthermore, NDRG2 expression level is significantly correlated with astrocyte senescence, and NDRG2 can directly interact with NF-κB and inhibit the nuclear import and DNA-binding activity of the NF-κB p65 subunit in primary astrocytes ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The serum-free medium was substituted with the complete medium and further incubated for 48 hours. Next, the cellular RNA was separated to verify the transfection validity [ 25 ]. Vectors, CAB39, Si-NC, and Si-CAB39 were devised and integrated by GenePharma (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%